Wind tunnel bench test of a pitch-and-plunge aeroelastic model undergoing nonlinear post-flutter oscillations - Santos, Matheus Martines dos [UNESP]; Adeodato, Arthur; Dağlı, Osman; de Sousa, Vagner Candido [UNESP] (Springer Nature, 2024)
The nonlinear post-flutter aeroelastic behavior of a classical pitch-and-plunge airfoil model in low-speed wind tunnel bench tests is reported in this study for a range of airflow speeds where stable oscillations are observed. An experimental airfoil prototype is designed, characterized and evaluated. Time domain data of the airfoil motion as well as other pertinent frequency and bifurcation characteristics are presented for different values of airflow speed, starting at the critical linear flutter speed of the airfoil model and increasing up to the sudden manifestation of violent unstable oscillations (when the test is interrupted for the safety of the structural apparatus). Stable post-flutter nonlinear oscillations, mainly attributed to the dynamic stall phenomenon and in a lesser degree to hardening structural effects, are observed for a range of airflow speeds starting at the neutral stability boundary of the aeroelastic system. The amplitudes of oscillation increase with increasing airflow speed and settle onto a limit-cycle. The coupled frequency of oscillation is dominated by the plunge degree-of-freedom and also increases with increasing airflow speed. The observed critical airfoil cut-in speed of limit-cycle onset is about 8.1 m/s (reduced speed of 5.1), and the observed cut-out speed of unstable response is about 9.5 m/s (reduced speed of 6.0). This work contributes with the literature of Aeroelasticity by presenting the realization, evaluation, and wind tunnel test data of a pitch-and-plunge airfoil model undergoing nonlinear post-flutter oscillations that may be useful to support other studies for verification purposes of eventual numerical simulations of similar aeroelastic systems.
Keywords: Dynamic stall; Nonlinear aeroelasticity; Post-flutter oscillations; Stall-induced oscillations